Guidance in Corrective Institutions in an Effort to Prevent Recidivice Drug Injury in Class II B Prison, Langsa City (Case Study of Class II B Corrective Institution, Langsa) - Dini Ayu Shafira; Marlina; Vita Cita Emia Tarigan (Universitas Efarina, 2025)
Correctional institutions used to be underestimated as institutions that facilitate the provision of punishments and the suspension of freedom of crime suspects. Of course, this should not happen again because it will decline the Correctional Institution as an institution that plays a role in fostering inmates and making them reborn into good and trustworthy human beings. The objectives of this research include. To find out and analyze the implementation of coaching activities for narcotics recidivist offenders in the Langsa Class IIB Correctional Institution and the obstacles of the Langsa City Class II B Correctional Institution in providing guidance to narcotics inmates who are committed recidivists. The research method used in this study is empirical normative, then the research is descriptive analytical, and uses a legislative and conceptual approach in solving problems. The data sources in this study consist of secondary data and primary data. The results of the study stated that the implementation of coaching activities for recidivist offenders in the Langsa Class IIB Correctional Institution has not been carried out optimally, this is because no special efforts have been made to narcotics inmates and the constraints of the Langsa City Class II B Correctional Institution in providing guidance to recidivist inmates lie in the facilities and infrastructure that are insufficient to carry out optimal coaching.